THE ROLE AND IMPACT OF DIGITAL TRANSFORMATION ON THE DEVELOPMENT OF SMALL AND MEDIUM-SIZED ENTERPRISES IN HAJDÚ-BIHAR COUNTY - Bogdán, Mihály; Popovics, Péter (Applied Studies in Agribusiness and Commerce, 2025)
In our survey-based research, assessed the opinions of 39 small and medium-sized enterprise (SME) leaders in Hajdú-Bihar County on digitalization, how they evaluate their employees' digital skills, what digital best practices they apply, and how familiar they are with current trends in digital best practices. In the literature review, we touch on the concepts and significance of digitalization and digital transformation, the characteristics and types of best practices, benchmarking as a tool for identifying them, and the steps involved in their implementation. We introduced five currently popular digital best practices: optical character recognition, homomorphic encryption, robotic process automation, intelligent process automation, and blockchain technology. The advantages and impact of these practices on corporate efficiency are highlighted. Based on the results, we reached the following conclusions:The findings show that most Hungarian companies view digitalization as an opportunity, but there are deficiencies in strategic planning and commitment. Although leaders theoretically support technological progress, 93% of companies do not have a developed digital strategy, and leaders also rate employee engagement as low. The resources allocated for digitalization investments are also low, with most companies spending only between 0-10 million HUF. The application of artificial intelligence (AI) technologies is still in its early stages, though there are positive examples. Dissatisfaction is evident regarding employees' digital competencies, particularly in problem-solving and data security. The lack of knowledge of modern digital technologies also hinders innovation. Companies' digital maturity is low, with most having only taken initial steps in this area. Often, the perceived digital intensity of the industry does not reflect reality, which can hinder development.